Estimating the crime effects of raising the age of majority: evidence from Connecticut - Loeffler, Charles E. (Criminology & public policy, 2016)
The results of recent empirical research have shown that juveniles do not achieve complete psychosocial maturity until postadolescence and that processing juveniles as adults in the criminal justice system can be associated with elevated rates of criminal recidivism. In response to these as well as other concerns, several states have recently raised their legal ages of majority in the hopes of reducing juvenile offending rates. Connecticut enacted one such law change when it raised its age of majority from 16 to 17 in 2010 and then from 17 to 18 in 2012 for all but the most serious offenses. The effect of Connecticut's policy change on juvenile crime is examined in this study. To discern between changes in juvenile offending and changes in the propensity of police to arrest youthful offenders in the aftermath of a law change, we use two methodological approaches. Synthetic control methods are used to generate triple‐differences estimates of the effect of Connecticut's policy change on juvenile arrests and overall crime rates by using a weighted average of other U.S. states as a natural comparison group. Next, by analyzing National Incident‐Based Reporting System (NIBRS) data for a subset of Connecticut's local jurisdictions, we examine changes in age‐specific juvenile arrests and changes in age‐specific juvenile offending. The resulting evidence suggests that no discernable change in juvenile offending occurred. In addition, evidence exists that in some Connecticut jurisdictions, officer, rather than juvenile, behavior was impacted by this law change.